An adept segmentation algorithm and its application to the extraction of local regions containing fiducial points - Ince, Erhan AliRiza; Ali, Syed Amjad (Springer-Verlag Berlin, 2006)
Locating human fiducial points like eyes and month in a frontal head and shoulder image is an active research area for applications such as model based teleconferencing systems, model based low bit rate video transmission, computer based identification and recognition systems. This paper proposes an adept and efficient rule based skin color region extraction algorithm using normalized r-g color space. The given scheme extracts the skin pixels employing a simple quadratic polynomial model and some additional color based rules to extract possible eye and lip regions. The algorithm refines the search for fiducial points by eliminating falsely extracted feature components using spatial and geometrical representations of facial components. The algorithm described herein has been implemented and tested with 311, images from FERET database with varying light conditions, skin colors, orientation and tilts. Experimental results indicate that the proposed algorithm is quite robust and leads to good facial feature extraction.
21st International Symposium on Computer and Information Sciences (ISCIS 2006) -- NOV 01-03, 2006 -- Istanbul, TURKEY
Keywords: Face-Recognition